Stability assessment of underground openings using different rock support systems (Rudarsko-geološko-naftni zbornik, 2019)
Rock support systems have become widely dominant components in underground hard rock mines. They are used to maintain the stability of underground openings and reinforce disturbed rock masses after creating an excavation or start- ing mining activity. Thus, the objective of this study is to examine the effect of support types on the performance stabil- ity of underground tunnels that exist in hard rock mines, in terms of deformation, the extent of failure zones and the strength of the rock mass surrounding the tunnel. This, in turn, will help in the selection of an appropriate support system that mitigates the stress-deformation conditions around the tunnel. Herein, four models have been built using the RS2D program, simulated and introduced to evaluate the behaviour of an underground tunnel with different rock support systems. The first model is simulated without any support system, whereas, rock bolts have been installed in the second model. The third model applied only shotcrete, while rock bolts and shotcrete are combined together in the fourth model. The results are presented and discussed in terms of strength factor, the extent of yielding zones and rock mass displacement/convergence. The results show that tunnel stability suffers when there is no rock support at all, while, it is significantly improved when the rock support system is installed. The optimum improvement is obtained when both shotcrete and rock bolts are employed together.